ORGANIZATIONAL AND PROFESSIONAL FACTORS OF PERFECTIONISM IN SCIENTIFIC AND PEDAGOGICAL STAFF OF HIGHER SCHOOL - Grubi, Tamara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The attention to the study of perfectionism in high school in Ukraine can be explained with modernization and development of Ukrainian higher education, as an access to the European educational research environment. The interest to the perfectionism in scientific and pedagogical staff of high school can be explained by new requirements for professional activity and these factors demand from a teacher of higher school can be an achievement of new standards, obtaining successfully by focusing on avoiding failures. The study is conducted within the pedagogy field. In this article, the author identifies and analyzes the impact of social-demographic factors (such as age, gender, place of residence), organizational and professional factors (such as job experience, academic degree, post, direction of teaching activity, number of students, level of famousness of higher school, level of social-psychological climate etc.). The four manifestations of perfectionism, which are: -     Absence of perfectionism - where normal and pathological perfectionism are represented at a low level. -     Perfectionism with negative orientation - consists of the respondents with pathological type of perfectionism.-     Ambivalent perfectionism - included the respondents in which the pathological and normal types of perfectionism are equally highly represented. -     Perfectionism with positive orientation - consists of the respondents with manifestations of normal type of perfectionism.